2017
DOI: 10.3382/ps/pew407
|View full text |Cite
|
Sign up to set email alerts
|

Gp85 genetic diversity of avian leukosis virus subgroup J among different individual chickens from a native flock

Abstract: To compare the genetic diversity and quasispecies evolution of avian leukosis virus (ALV) among different individuals, 5 chickens, raised in Shandong Provice of China, were randomly selected from a local chicken flock associated with serious tumor cases. Blood samples were collected and inoculated into chicken embryo fibroblast and DF-1 cell lines for virus isolation and identification, respectively, of Marek's disease virus (MDV), reticuloendotheliosis virus (REV), and ALV. Five strains of ALV subgroup J (ALV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…This may be because of the instability and diversity of the Retroviridae ( Garcia-Montojo et al., 2018 ) and the rapid evolution of the virus to help it escape the immune protection mechanisms of the host by the gene mutations and reorganization of the genome ( Zhang et al., 2018 ). During the process of ALV-J transmission and spread all over the world, the ALV-J genome is constantly changing ( Ji et al., 2012 , Li et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be because of the instability and diversity of the Retroviridae ( Garcia-Montojo et al., 2018 ) and the rapid evolution of the virus to help it escape the immune protection mechanisms of the host by the gene mutations and reorganization of the genome ( Zhang et al., 2018 ). During the process of ALV-J transmission and spread all over the world, the ALV-J genome is constantly changing ( Ji et al., 2012 , Li et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lin [ 27 ] isolated 12 strains of avian leukosis virus subgroup J from chickens in south China during 2013–2014 and detected several amino acid variations and potential glycosylation sites in gp85 by sequencing. In addition, they found that many genetic variations of the gp85 exist in an indigenous chicken flock [ 17 ]. The monitoring of ALV in local chickens in our country has been continuous; simultaneous, our laboratory has executed the purification of ALV-J from indigenous chickens.…”
Section: Discussionmentioning
confidence: 99%
“…A measure of success has been achieved in the purification, prevention, and control of ALV among white-feathered broilers and layer chickens since the purification of ALV was executed in China. But there are many breeds with excellent characteristics in China, these chickens are still susceptible to ALV-J infection [ 17 , 18 ].Thus, to grasp the quasispecies evolution of ALV in a flock of chickens of local breed and accelerate the purification of ALV in China, this study isolated and identified the viruses from a local chicken farm during the process of purifying ALV and the molecular characteristics of env and LTR were determined and analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…RNA viruses are also divided into avian, mammalian, and zoonotic viruses in domestic animal industries. For example, the avian leukosis retrovirus causes great losses in the avian industry and many subgroups have been isolated in recent years (6)(7)(8)(9)(10)(11)(12). In mammals, more RNA viruses are also being reported, of which the classical swine fever virus and porcine reproductive and respiratory syndrome virus (PRRSV) are the main RNA viruses that cause great losses in porcine industries.…”
Section: Diseases Caused By Rna Viruses In the Livestock Industrymentioning
confidence: 99%